Al-Washl dan Al-Fashl dalam Kitab Ar-Risalah Imam asy-Syafi'i - Fajar Lazuardi; Raswan; Dardiri (Indo Publishing, 2025)
This study aims to analyze the application of Al-Washl and Al-Fashl in the chapter “Bayān” of the Ar-Risālah by Imām al-Shāfiʿī. Al-Washl (connection) and Al-Fashl (separation) are two essential concepts in the science of Maʿānī, a branch of Arabic rhetoric (Balāghah) that deals with the rules of linking and separating sentences. Understanding these two concepts is crucial, as they significantly affect the clarity of meaning and eloquence in Arabic expression. Although many studies have addressed Al-Washl and Al-Fashl, this research presents a novel contribution by focusing on Ar-Risālah as the primary object of study—an approach that has rarely been explored from this perspective. Employing a qualitative descriptive design, the researcher systematically analyzes each sentence in the “Bayān” chapter to identify and classify their usage according to the principles of Washl and Fashl